Fibromuscular Dysplasia of the Coronary Arteries: A Case Report and Review of the Literature - Julia KUZYK; Oksana BOIKO; Taras STETSKO (Federation of Turkish Pathology Societies, 2018)
Fibromuscular dysplasia is a nonatherosclerotic and non-inflammatory vascular disease with primary lesion of renal and internal carotid arteries. We present a neonatal case of fibromuscular dysplasia who died on the second day of life. The newborn suffered from fibromuscular dysplasia of the coronary arteries and a congenital heart defect. The interesting feature of this case was the formation of aneurysms of the coronary arteries with pulmonary atresia. This case demonstrates a casuistically rare form of association between fibromuscular dysplasia of the coronary arteries and pulmonary artery atresia.